Drums Sound in Hackensack: Agnes de Mille and the Jooss Ballet. Issue 2 (4th May 2019) - Lidbury, Clare
Abstract: In 1941 Agnes de Mille created Drums Sound in Hackensack for the Jooss Ballet. There is no film of the work and few photographs, but the work is documented in her choreographic notes, letters to and from de Mille, dancers' recollections, and reviews. From these we can learn why and how de Mille created the work, what it was like, and why it was significant to the Jooss Ballet. With its American theme, historical setting, dream sequence, and a female character at the center of the work, it may be seen as a forgotten stepping stone in de Mille's choreographic development.